Correlation between Sonoelastography and Histopathological Findings in Evaluation of Chronic Renal Allograft Disease - Bhandari, R. M.; Suwal, S.; Chataut, D.; Ansari, M. A. (Kathmandu University Medical Journal, 2022)
Background Non-invasive evaluation tool for allograft kidney is important to predict chronic allograft dysfunction as it can be alternative to the invasive biopsy which is prone to so many complications. Sonoelastography can assess the stiffness of the allograft renal parenchyma, which is prone to undergo interstitial fibrosis. Objective To correlate sonoelastography with histopathology findings in the renal allografts. Method Sonoelastography was done in 60 renal allograft recipients prior to their biopsy for various indications. Estimated glomerular filtration rate (eGFR) of the patient were also obtained. Histopathology reports were collected to determine Banff score of interstitial fibrosis. Descriptive measurements (Mean ± standard deviation, Frequencies, Proportions) were calculated. Correlations among the variables were measured using Pearson’s correlation, independent sample t-test, and ANOVA. Result The mean strain index (SI) was lower in higher grades of fibrosis. There was significant difference in mean SI (F=18.264; df= 2,57; p < 0.001) among the histological grades of fibrosis. Also a significant difference in SI among mild and moderate (S.E. 0.27, p value < 0.001), mild and severe (S.E. 0.213, p value < 0.001) as well as moderate and severe fibrosis (S.E. 0.244, p value < 0.001) was seen. Significant correlation of eGFR with SI (p < 0.001) was also seen. Conclusion Strain index, measured with sonoelastography, significantly correlated with different grades of tissue fibrosis. Thus it can be used as alternative method for evaluation of renal allograft patients to avoid complications of biopsy.